Marketing Strategy Based on Image of Hang Tuah University Dental and Oral Hospital in 2015 - Annisa Mutiara Pertiwi; Dwi Hariyanto; Aprilia (Denta Journal Kedokteran Gigi, 2017)
Background: Individuals in our contemporary society tend to depend on various types of services, including health care service. Managers of health care services must be aware of this situation to improve image and reputation as a public’s choice services. Image is an award obtained by a company for their excellence in services. In improving the image, a company needs the public’s or consumer’s appraisals for a marketing strategy formation. Purpose: As information to develop the image of Dental and Oral Hospital of Hang Tuah University, Surabaya. Materials and Methods: descriptive analysis with cross sectional research design was used in this study. Simple random sampling of probability sampling technique was used to choose 100 respondents of this study. Respondents were given a questionnaire to assess the image of Dental and Oral Hospital, Hang Tuah University Surabaya. The results of the questionnaire were analyzed by using descriptive statistics. Result: Results on the image of Dental and Oral Hospital of Hang Tuah University showed that 83 respondents rated moderately good image, while 17 respondents rated poor image. Conclusion: Based on the SWOT matrix, it can be concluded that several development through consideration of internal and external factors can be beneficial to the progress of Dental and Oral Hospital of Hang Tuah University, Surabaya.